Two-dimensional design and analysis of centrifugal blood pump impeller - Koh, Choon Peng. (2008)
The objective for impeller's blade curvature design is to achieve high efficiency and head generation for the pump, while at the same time minimising the highly sheared turbulent flow within the pump. The blades' curvatures are assumed to have constant thickness and were modelled numerically. The numerical results are agreeable to experimental data. Investigations are carried out to determine the optimal blade number, the type of blades and the impeller's rotational speed. It was found that, in general, impellers with 10 blades generate the highest-pressure head. The flow pattern observed from the velocity vectors showed the existence of large vortices produced by forward facing blades leading to high shear stress.